(3GdYdGbGJ GdEbJUGOjI GdOhdjI (B:s (3OQGSI deXGgQ heTcdGJ GdGbJUGO GdOhdi GdeYGUQ habG ddJWhQGJ GdWGFdI Ydi GdfXGe GdGbJUGOi GdYGdei GdLOjO hGdeSJLOGJ PGJ GdYdGbI HeYGdeg GdfbOjI hGdeGdjI hGdJLGQjI (B/s - (3MTjT, YGOd CMeOs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2000)
(3eGgjI hCgejI GdYdGbGJ GdEbJUGOjI GdOhdjI heOi JejRgG Yf YdGbGJ GdEbJUGO GdOGNdj(B- (3CSS bjGe GdJHGOd GdOhdj ajeG Hjf eNJda GdOhd hGdCgejI GdfSHjI ddJLGQI GdNGQLjI HGdfSHI ddEbJUGO Gdbhej(B- (3GdedGeM hGdNUGFU GdeMOOI dWHjYI GdEbJUGO GdYGdej GdeYGUQ HeQYGI GdJWhQGJ GdWGQFI Ydi GdYdGbGJ GdEbJUGOjI GdOhdjI(B- (3JSLjd GdeYGedGJ GdEbJUGOjI GdeJQJHI Ydi bjGe GdJHGOd GdOhdj HhGSWI ejRGf GdOGFfjI hGdeOjhfjI hejRGf GdeOahYGJ GdOhdjI(B- (3JShjI GdeOahYJ GdOhdjI ef NdGd Shb GdUQa GdCLfHj hGdfXe GdeJYGQa YdjgG aj JMOjO CSYGQ GdYedGJ aj gPg GdShb(B- (3GdSjhdI GdOhdjI hOhQ UfOhb GdfbO GdOhdj GdeJYdb HMd eG JKjQg ef eTcdGJ heG JJVefg JShjI eOahYGJ GdOhd GdeJbOeI hGdHdOGf GdfGejI(B- (3Jehjd GMJjGLGJ GdJYejQ hGdJfejI ef NdGd GdeDSSGJ GdJGHYI ddHfc GdOhdj(B- (3GdSjGSGJ GdJLGQjI GdMGceI ddeHGOdGJ GdOhdjI hGNJdGa eVehfgG HCNJdGa GdfXe hGdChVGY GdEbJUGOjI GdSGFOI(B- (3GdhSGFd hGdCSGdjH GdafjI(B- (3GJaGbjGJ JMQjQ GdJLGQI hGdeHGOdGJ GdOhdjI GdeYQhaI HGdfXGe GdLGJ(B- (3efXeI GdJLGQI GdYGdejI hGdegGe GdeSfOI GdjgG aj EOGQI hJSjjQ GdeHGOdGJ GdOhdjIs
(3HjHdjhZQGajG(B: (3U(B.350- 355s
Keywords: (3EbJUGO Ohdjs; (3GdJLGQI GdNGQLjIs; (3UfOhb GdfbO GdOhdjs